Knowledge and Competences of Racket Sport Coaches: what do they think and know? - Mairin Del Corto Motta; Júlia Barreira; Caio Corrêa Cortela; Larissa Rafaela Galatti (Universidad de Granada, 2021)
This study analyzed the professional, interpersonal and intrapersonal knowledge as well as the competences considered most  important to Brazilian coaches who work with four different racket sports (badminton, squash, tennis and table tennis). A total of 150 coaches (122 men and 28 women) participated in this study, most of whom were tennis coaches (47%), followed by badminton (28%), table tennis (16%) and squash (12%). For data collection, a socio-demographic questionnaire and the Coaches' Knowledge and Competence Questionnaire (CKCQ) (Quinaud et. Al, 2018) were applied. The Wilcoxon test was used to compare the importance and domain attributed by the coaches to the items. In general, knowledge and competences had high scores of attributed importance and perceived domain, however the knowledge of program implementation and evaluation, professional development of coaches and the competence to develop the coaching philosophy had the lowest values of perceived domain.